The protective efficacy of dual dietary rosemary plus cinnamon mix against lead nitrate-induced immune suppression, genotoxicity, and oxidant/antioxidant status in Nile tilapia fingerlings - Mohsen Abdel-Tawwab; Hiam Elabd; Heba H. Mahboub; Mohamed Ezzat M. Assayed; Heba S. Hamed; Asmaa Elsayyad; Engy M. M. Mohamed (Aquaculture International, 2024)
Lead (Pb) is a common heavy metal, which negatively influences the health and performance of aquatic organisms. The aquatic pollution with Pb is increasing day after day due to the increase in human activities, agricultural, and mining activities among others. Lead was regarded as oxidative stressor causing mutagenic and physiological disorders in aquatic animals. Hence, the current perspective assessed the promoting effects of dietary mixture of rosemary plus cinnamon (R + C) intervention on growth, hemato-biochemical, and hepatic oxidative biomarkers in Nile tilapia ( Oreochromis niloticus ) exposed to a sub-lethal dose of lead nitrate (7.94 mg Pb/L) for 60 days. Fish were distributed into four equal groups; T1 was kept as a control group, T2 was fed on 10 g R + C/kg feed, and T3 and T4 were fed on the control diet and 10 g R + C/kg feed, respectively, along with lead nitrate exposure. Findings of the present study indicated that, upon exposure to Pb (T3), growth, hemato-biochemical, and immune indices in Nile tilapia were notably reduced compared with that of the control group (T1). Meanwhile, stress (blood glucose, cortisol, total cholesterol, lactate dehydrogenase, alanine and aspartate aminotransferase, and alkaline phosphatase), hepatic oxidative stress (superoxide dismutase, catalase, and glutathione peroxidase) biomarkers, and DNA fragmentation percentage were significantly augmented in T3 vs T1. Additionally, exposing fish to lead nitrate caused immune suppression compared with the control group (T3 vs T1). On the other hand, the dietary supplementation of R + C mix to Nile tilapia (T2) enhanced its growth performance, antioxidant, and immune status. Feeding Pb-intoxicated Nile tilapia on R + C mix (T4) mitigated the oxidative damage and immune suppression induced by lead nitrate exposure compared with T3. Based on the present study outcomes, we opine that feeding Nile tilapia with rosemary plus cinnamon mixture (10 g/kg feed) has protective effects against lead nitrate-induced stress, physiological alterations, and oxidative damage.